2013
DOI: 10.1021/ac4001942
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of dsDNA-Templated Copper Nanoparticles by Pyrophosphate as a Label-Free Fluorescent Strategy for Alkaline Phosphatase Assay

Abstract: On the basis of the inhibition of double strand DNA (dsDNA)-templated fluorescent copper nanoparticles (CuNPs) by pyrophosphate (PPi), a novel label-free turn-on fluorescent strategy to detect alkaline phosphatase (ALP) under physiological conditions has been developed. This method relies on the strong interaction between PPi and Cu(2+), which would hamper the effective formation of fluorescent CuNPs, leading to low fluorescence intensity. The ALP-catalyzed PPi hydrolysis would disable the complexation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(106 citation statements)
references
References 28 publications
3
103
0
Order By: Relevance
“…It has been reported that phosphate group containing compounds, such as the PPi hydrolysis product Pi, can inhibit the activity of ALP, as it will compete with PPi to bind with the active site of ALP [27]. Therefore, the inhibition effect of Pi on ALP activity was studied.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that phosphate group containing compounds, such as the PPi hydrolysis product Pi, can inhibit the activity of ALP, as it will compete with PPi to bind with the active site of ALP [27]. Therefore, the inhibition effect of Pi on ALP activity was studied.…”
Section: Resultsmentioning
confidence: 99%
“…Since it was reported by Mokhir et al in 2010, dsDNA-templated CuNPs have attracted great attention in fluorescence analysis of biomolecules for its facile synthesis and excellent optical properties [26][27][28][29]. In this paper, we have employed electrochemical technique as a substitution of fluorescent technique to characterize the formation of dsDNA-templated CuNPs for the development of an improved new aptasensor.…”
Section: Introductionmentioning
confidence: 98%
“…Alkaline phosphatase catalyzes dephosphorylation process of proteins, nucleic acids and small molecules, which can be found in a variety of tissues (liver, intestine, kidney, bone, and placenta) [1][2][3]. As an important diagnostic enzyme, ALP has long been identified as an important biomarker for clinical diagnostics [4].…”
Section: Introductionmentioning
confidence: 99%